Derived tame and derived wild algebras - Drozd, Y.A. (Algebra and Discrete Mathematics, 2004)
We prove that every finite dimensional algebra over an algebraically closed field is either derived tame or derived wild. We also prove that any deformation of a derived wild algebra is derived wild.